Histochemical Heterogeneity of Secretory Structures in the Flowers of Lysimachia nummularia L. - Radchenko, Volodymyr; Likhanov, Artyr; Matyashuk, Raisa (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The study of flowers of Lysimachia nummularia L. showed that glandular trichomes are formed on the stamen filaments, as well as on the adaxial and abaxial surfaces of the sepals and petals. The polyfunctionality of trichomes in plants Lysimachia nummularia are based on the biochemical and anatomical heterogeneity of cells and secretory structures, which are a functional component of the ecological plasticity of the species. Accumulation of phenolic compounds in the tissues of leaves, stems and flowers begins at the early stages of plant development. Secondary metabolites are localized in the cytoplasm of the cells of the upper and lower epidermis of the leaves, in the parenchyma of the stems of brephical plants. A significant amount of condensed polyphenolic compounds are found in cells of the parenchyma of the receptacle, the integumentary tapetum and the epidermis of the petals in the surrounding polysaccharides. They act as a chemical barrier, which slows down the oxidation of phenols. A significant number of pectins and glycans were found in the cells of the glandular trichomes. A certain spatial uneven distribution of polysaccharides in the external secretory structures is established. It is shown that they are concentrated in the basal cells of the legs and are almost completely absent in cells that are directly linked to the secretory head. Their cell walls are thin and almost completely formed by pectins. This creates the prerequisites for easy head breaking along with secretory fillers. Under such conditions, when they are harvested by bees, the risk of premature leakage, oxidation and polymerization of biologically active compounds is reduced. Polysaccharides in the cells of the secretory epithelium can be considered as the basis for the creation of a biopolymer film with bactericidal and fungicidal components that use bees when facing cell nests. It was found out that the cell components of the trichome head are capable of intense autofluorescence in blue, blue-green and green spectrums. The expressed structural and biochemical heterogeneity of micromorphological elements of the secretory system of plants Lysimachia nummularia is physiologically and ecologically related to their functions. In our opinion, these functions can be much more complicated than it was thought up to this day. Among these, their direct or indirect participation in the work of systems of extracellular and long-distance signaling, regulation of forage and nesting behavior of insects cannot be excluded.